Acute Hypertriglyceridemia in Patients with COVID-19 Receiving Parenteral Nutrition - Villa López, Gema (Nutrients, 2021)
Hypertriglyceridemia is a metabolic complication associated with parenteral nutrition (PN). It is unknown if patients with acute respiratory distress syndrome (ARDS) secondary to COVID-19 are more at risk. Our aim was to describe the incidence, risk factors and clinical impact of hypertriglyceridemia in critically ill patients with ARDS-COVID-19 receiving PN. We designed a cohort study of patients with ARDS-COVID-19 infection that required admission to critical care units and nutritional support with PN. Individual PN prescriptions for macronutrients and insulin were provided. Lipid emulsion contained fish oil (SMOFlipid(®) or Lipoplus(®)). Hypertriglyceridemia was defined as plasma levels above 400 mg/dL. Eighty-seven patients, 66.6% men, 60.1 ± 10.8 years old, BMI 29.1 ± 5.6 kg/m(2), 71% of whom received lopinavir/ritonavir, 56% received Propofol and 55% received Tocilizumab were included. The incidence of hypertriglyceridemia was 37 × 100 patient-days with PN. This complication was more frequent in obese patients (OR 3.34; 95% CI, 2.35–4.33) and in those treated with lopinavir/ritonavir (OR 4.98; 95% CI, 3.60–6.29) or Propofol (OR 2.45; 95% CI, 1.55–3.35). Total mortality was 33.3%, similar between the type of lipid emulsion (p = 0.478). On average, patients with hypertriglyceridemia had a longer requirement of PN compared to the group without elevated triglycerides (TG), probably because of their longer survival (p = 0.001). TG higher than 400 mg/dL was not a protective factor for mortality (OR 0.31; 95% CI, 0.01–1.30). In conclusion, the incidence of hypertriglyceridemia was 37 × 100 patient-days with PN. The risk of this complication is associated with obesity and the use of lopinavir/ritonavir or Propofol.